Status and Compliance of Senior High School Voucher Program among Private Schools in NCR: A Quality Assurance Review (International Journal of Scientific Research and Management (IJSRM), 2024)
The Enhanced Basic Education Act of 2013, often known as K to 12, was introduced by Republic Act10533. The SHS voucher program is a mechanism to provide financial assistance to qualified students while also decongesting public schools and promoting partnerships with private schools. In response to the mandate of RA 10533 to expand Government Assistance to Students and Teachers in Private Education (E-GASTPE), the Department of Education (DepEd) introduced the Senior High School Voucher Program. This demonstrates that condensing the 12 years of education taught around the world into 10 years of education in the Philippines has been a struggle for students and teachers seeking to meet global standards; thus, the goal of the study is to uncover implementation issues, show best practices, and recommend appropriate interventions that can improve the execution of the Senior High School Voucher Program among Metro Manila private schools. The study utilized a descriptive method of research and descriptive correlational design. The study was participated by the DepEd Officials/Employees, School Administrators, and Stakeholders. This demonstrates that condensing the 12 years of education taught around the world into 10 years of education in the Philippines has been a struggle for students and teachers seeking to meet global standards; thus, the goal of the study is to uncover implementation issues, show best practices, and recommend appropriate interventions that can improve the execution of the Senior High School Voucher Program among Metro Manila private schools.